Didactic Design Analysis Of Quadrilateral Learning In The Term Of Interactive Media Based On Adobe Flash Through Contextual Teaching And Learning Approach : Analisis Desain Didaktis Pembelajaran Segiempat Berupa Media Interaktif Berbasis Adobe Flash Melalui Pendekatan Contextual Teaching And Learning - Erika, Erika; Sumarni, Sumarni; Adiastuty, Nuranita (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
This research was conducted to see the alleged learning obstacle that appeared in the didactic design and provide a didactic design proposal to overcome the alleged learning obstacle. The type of research used is qualitative research with the Didactical Design Research (DDR) model, this research uses triangulation techniques and in the Didactical Design Research there are three stages of analysis, namely Prospective Analysis, conducting interviews with model teachers regarding didactic designs used at the time. In learning, Metapedadidactic Analysis is carried out by analyzing the didactic design that has been made by the model teacher, what learning obstacle is suspected and what causes it, Retrospective Analysis makes conclusions and didactic design proposals on the rectangular material. The subject of this research is the didactic design in the form of lesson plans and learning media that have been made by the model teacher. Based on the analysis, there is an assumption that learning obstacle appears in the didactic design, namely didactical learning obstacle and epistemological learning obstacle, resulting in a didactic design proposal to reduce learning obstacle.